CDA Cares: The Power of Community Action - Huong Le; Ariane Terlet (Journal of the California Dental Association)
When adult dental benefits were eliminated in 2009 for 3 million Medicaid-eligible adults under the Medi-Cal Dental Program (California’s Medicaid program), the California Dental Association Foundation created CDA Cares. This large scale, community-based, pop-up dental clinic was designed to meet the immediate emergent and nonemergent dental needs of some of California’s most vulnerable residents. Hundreds of volunteers participated in the two-day free care events, including dental professionals, dental students, oral health advocates, community members and CDA staff. Clinics were held around the state in large public venues, such as convention centers and fairgrounds, enabling volunteer dentists to alleviate dental pain and infection for thousands of people. Through CDA’s dedicated outreach to local policymakers and state legislators, the event also provided essential education on the importance of oral health and the overwhelming need for care in our state. These efforts successfully influenced the return of Medi-Cal dental benefits for California’s low-income adults. CDA Cares powerfully proved how working together could produce results that otherwise would not have been achieved by individual efforts alone.